Lack of breast feeding and early weaning in infants of Asian immigrants to Wolverhampton. Issue 8 (August 1976) - Evans, N; Walpole, I R; Qureshi, M U; Memon, M H; Everley Jones, H W
Abstract : Fifty Asian immigrant mothers who would have expected to breast feed their infants had they remained in rural Asia were studied. There was a striking reduction in the incidence and duration of breast feeding on arrival in the United Kingdom, and a fall in the age of weaning. The availability of an alternative to human milk is the most important factor reducing the incidence of breast feeding. Only 2 (4%) of the 46 infants followed prospectively were breast fed. Reasons for not breast feeding were sought and the results indicated that the majority of mothers were frightened, misinformed, or apathetic about breast feeding. If breast feeding is to be promoted, antenatal education and encouragement is essential. The advantages of human milk need to be stressed. Potentially serious mistakes occurred in preparing bottle feeds, and vitamin supplements were often inadequate. Later weaning could be encouraged by the staff of well baby clinics.